Research Trends and Hotspots on karst water resource in Iran and the world - Rahim Kazemi (Water Harvesting Research, 2021)
Karst groundwater is one of the primary water resources in most territories of Iran where karst topography is strongly featured. Understanding the key knowledge and research status of karst is an important prerequisite for subsequent research. This study aimed to examine the literature characteristics and research hotspots of karst based on Science direct database from 1998–2021 and scientific information database (SID) of Jihad Daneshgahi and Iranian Research Institute for Information Science and Technology (IranDoc). With systematic bibliometric analysis, insights were made into multiple aspects including research output, subject categories, journals, countries/territories, hotspots and research trends. The results showed that the general trend of global scientific publications in karst research has a negative slope with a negative growth rate of 0.91. But the trend of Iranian publications, with a positive slope and coefficient determination of 0.87 and a positive growth rate of 1.2 percent, has been increasing. The results of thematic classification of publications in the world showed that the most articles with 75.96% belong to research articles and the lowest to conference articles and editorials. Iranian articles also belong to the first order of importance to research articles with 91%, which is a larger share of the total articles than global articles. The results of analysis of the most important scientific journals related to karst showed that these journals have a very high h-index and JCR in Q1 and Q2. Keywords related to the intrinsic, structural characteristics and karst water resources systems had the highest frequency and the lowest frequency related to karst hazards.